Methane and ozone conditionality of the mass fires - Lyushvin P.B.; M. O, Buyanova (IJRDO-Journal of Applied Science, 2022)
The mass fires at the Earth’s surface are caused by both natural, and anthropogenic factors. Natural – the oxidation and decomposition of organic matter which is followed by allocation of energy at the complicated heat exchange, dry thunderstorms, solar radiation, a volcanic lava and meteors. Anthropogenic, including, along roads and settlements – from glass and other materials concentrating solar radiation or from the chemical reactions happening to them, stubs and also ritual. In Northern and Central Europe, moisture of Atlantic and a lawn low-growing grass preserves against growth of the fires that evaporates moisture many times less, than high wild-growing in the east of the continent. Allocating the abnormal maintenance (concentration) of one of factors at a background condition of the others it is possible to estimate its regional importance for emergence growth of the fires. It turned out that ignitions along highways and in mountains are most characteristic, Massawa - in zones of the increased concentration of methane and other flammable substances (essential oils) at the magnetized breaks of earth crust. The role of weather and solar radiation for efficiency of ignitions increases at reduction of humidity of air, especially it is shown in mountain conditions and in ozone holes where the contribution of high-energy ultra-violet radiation many times increases. It is reached by concentration of the ultra-violet site of a rainbow by atmospheric magnifying glasses (thermo-optical effect) or the combined fields of several reflections of ultraviolet ("sunbeams", from drops of water or crystals of ice).